Exosome‐derived circTFDP2 promotes prostate cancer progression by preventing PARP1 from caspase‐3‐dependent cleavage. Issue 1 (3rd January 2023) - Ding, Lifeng; Zheng, Qiming; Lin, Yudong; Wang, Ruyue; Wang, Huan; Luo, Wenqin; Lu, Zeyi; Xie, Haiyun; Ren, Liangliang; Lu, Haohua; Yu, Chenhao; Zhang, Jixuan; et al.
Abstract: Background: Circular RNAs (circRNAs) have been reported to play a significant role in tumorigenesis. However, the detailed function of circRNA in prostate cancer (PCa) is still largely unknown. Methods: We quantified circTFDP2 expression in PCa tissues and adjacent normal tissues using quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Colony formation, Cell Counting Kit‐8 (CCK‐8), flow cytometry, transwell, and in vivo progression and metastasis assays were applied to reveal the proliferation and metastatic abilities of circTFDP2 in PCa cells. Mass spectrometry, RNA pulldown, RNA‐immunoprecipitation (RIP), western blotting and immunofluorescence were used for the mechanistic studies. qRT‐PCR and RIP assays were used to explore the regulatory role of eIF4A3 in the biogenesis of circTFDP2. Finally, functional assays showed the effect of circTFDP2‐containing exosomes on PCa cell progression. Results: circTFDP2 was upregulated in PCa tissues compared with adjacent normal tissues. Furthermore, high circTFDP2 expression was positively correlated with the Gleason score. Functionally, circTFDP2 promoted PCa cell proliferation and metastasis both in vivo and in vitro. Mechanistically, circTFDP2 interacted with poly(ADP‐ribose) polymerase 1 (PARP1) protein in its DNA‐binding domain to prevent it from active caspase‐3‐dependent cleavage, and finally relieved PCa cells from DNA damage. In addition, RNA‐binding protein eIF4A3 can interact with the flanking region of circTFDP2 and promote the biogenesis of circTFDP2. Moreover, exosome‐derived circTFDP2 promoted PCa cell progression. Conclusions: In general, our study demonstrated that circTFDP2 promoted PCa cell progression through the PARP1/DNA damage axis, which may be a promising therapeutic target for PCa. Abstract : 1. circTFDP2 is upregulated in prostate cancer tissues and positively correlated with the Gleason score, metastasis status and T stage of prostate cancer patients. 2. circTFDP2 promotes prostate cancer progression via directly binding to PARP1. 3. circTFDP2 could be secreted to the cell culture by exosomes.